Discover answers to your most pressing questions at Westonci.ca, the ultimate Q&A platform that connects you with expert solutions. Ask your questions and receive detailed answers from professionals with extensive experience in various fields. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.

Solve equation in one variable algebraically

-2 (3x-1) + x = 14-x


Sagot :

Answer: x = -3

Step-by-step explanation:

Given expression

-2 (3x - 1) + x = 14 - x

Expand parentheses and apply the distributive property

-6x + 2 + x = 14 - x

Combine like terms

(-6x + x) + 2 = 14 - x

-5x + 2 = 14 - x

Add x on both sides

-5x + 2 + x = 14 - x + x

-4x + 2 = 14

Subtract 2 on both sides

-4x + 2 - 2 = 14 - 2

-4x = 12

Divide -4 on both sides

-4x / -4 = 12 / -4

[tex]\boxed{x=-3}[/tex]

Hope this helps!! :)

Please let me know if you have any questions